Magnetically enhanced mechanical and creep properties of a structural epoxy. (22nd September 2009) - Tehrani, Mehran; Al-Haik, Marwan
The current investigation presents the benefit influence of the magnetic processing of a structural epoxy system via moderate permanent magnetic field. During the curing process of a liquid-crystalline epoxy resin, a magnetic field of 0.5 Tesla was applied, and the mechanical properties of the cured resin were investigated using nanoindentation and nanocreep tests. Compared to samples processed without magnetic field under the same thermal conditions, the magnetically processed samples show an improvement in their modulus, hardness and creep resistance. The two-dimensional stretching of both main chains and the crosslinks of the amorphous epoxy – due to the applied magnetic field – is shown to improve the properties along both the parallel and lateral directions of the applied field.